Circulating Biomarkers for Monitoring Chemotherapy-Induced Cardiotoxicity in Children - Luigia Meo; Maria Savarese; Carmen Munno; Peppino Mirabelli; Pia Ragno; Ornella Leone; Mariaevelina Alfieri (MDPI AG, 2023)
Most commonly diagnosed cancer pathologies in the pediatric population comprise leukemias and cancers of the nervous system. The percentage of cancer survivors increased from approximatively 50% to 80% thanks to improvements in medical treatments and the introduction of new chemotherapies. However, as a consequence, heart disease has become the main cause of death in the children due to the cardiotoxicity induced by chemotherapy treatments. The use of different cardiovascular biomarkers, complementing data obtained from electrocardiogram, echocardiography cardiac imaging, and evaluation of clinical symptoms, is considered a routine in clinical diagnosis, prognosis, risk stratification, and differential diagnosis. Cardiac troponin and natriuretic peptides are the best-validated biomarkers broadly accepted in clinical practice for the diagnosis of acute coronary syndrome and heart failure, although many other biomarkers are used and several potential markers are currently under study and possibly will play a more prominent role in the future. Several studies have shown how the measurement of cardiac troponin (cTn) can be used for the early detection of heart damage in oncological patients treated with potentially cardiotoxic chemotherapeutic drugs. The advent of high sensitive methods (hs-cTnI or hs-cTnT) further improved the effectiveness of risk stratification and monitoring during treatment cycles.